Desain augmented reality laboratory based implement optical physics sebagai media pembelajaran fisika - Dwi Rizki Oktaviani; Salma Masturoh; Diana Devarainy; Riski Nurswandi; Irnin Agustina Dwi Astuti (Navigation Physics : Journal of Physics Education, 2021)
In the end of 2019, as a new period for the emergence of Corona Virus Disease 2019 (COVID-19) has made the world including Indonesia, limit movement in the social, economic, and even educational spheres. Indonesia has implemented PSBB (Large-Scale Social Restrictions) which resulted in activities such as being stopped working from being a WFH (Work From Home), and study from home. This learning media can help teachers to be more creative in delivering material so that it is not boring. Utilizing used goods as optical tools to make it easier for students to see objects or objects that are not necessarily visible to the eye. The purpose of this research is to develop learning media based on augmented reality, especially in the discussion of physics, namely optical tools that will make it easier for students during a pandemic, where physics practicum activities use used goods as a medium that will be made by students. Because, the pandemic has become an obstacle for students to carry out practical work directly in the laboratory.